GeoSpatial Visual Analytics Geographical Information Processing and Visual Analytics for Environmental Security - Amicis, Raffaele De.; Stojanovic, Radovan; Conti, Giuseppe; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
Access, distribution and processing of Geographic Information (GI) are basic preconditions to support strategic environmental decision-making. The heterogeneity of information on the environment today available is driving a wide number of initiatives, on both sides of the Atlantic, all advocating both the strategic role of proper management and processing of environme- related data as well as the importance of harmonized IT infrastructures designed to better monitor and manage the environment. The extremely wide range of often multidimensional environmental information made available at the global scale poses a great challenge to technologists and scientists to find extremely sophisticated yet effective ways to provide access to relevant data patterns within such a vast and highly dynamic information flow. In the past years the domain of 3D scientific visualization has developed several solutions designed for operators requiring to access results of a simulation through the use of 3D visualization that could support the understanding of an evolving phenomenon. However 3D data visualization alone does not provide model and hypothesis-making neither it provide tools to validate results. In order overcome this shortcoming, in recent years scientists have developed a discipline that combines the benefits of data mining and information visualization, which is often referred to as Visual Analytics (VA).
Spatial Data Infrastructures -- A Showcase of Spatial Data Infrastructures and Related Technologies -- Towards Interoperable Environmental Security Applications The Role of Open Geospatial Service Platform -- Signal and Data Processing -- Sorting Spatial Data by Spatial Occupancy -- Gis Model Applications for Sustainable Development and Environmental Planning at the Regional Level -- Application of Neural Networks In Image Processing and Visualization -- Data Processing for Heavy Metals Accumulation in Urban Areas -- A Multi-Criteria Decision Making Conceptual Approach to Optimal Landfill Monitoring -- Environmental Protection and Industry: Parameters Necessary for Environmentally Related Decision Making -- Time-Frequency Analysis for Sar and Isar Imaging -- Processing of Multichannel Remote Sensing Data for Environment Monitoring -- Earth Observation and Remote Sensing -- Exploiting Earth Observation Missions: Opportunities and Issues in Ground Segment Interfaces Harmonization -- Data Filtering and Data Fusion in Remote Sensing Systems -- Soil Mapper® Multi-Sensor and Multi-Temporal Applications for Semantic-Based Image Information Mining -- Cooperative Decentralization: A New Way to Build an Added Value Chain With Shared Multi-Resolution Satellite and Aerial Imagery and Geoinformation -- Cosmo/Skymed to Support MGCP Mapping -- Scientific Visualization -- Visual Processing of Geographic and Environmental Information in the Basque Country: Two Basque Case Studies -- Dynamic Terrains: Cities and Real-Time Video on Gigantic Terrain Models -- Digital Terrain Models: A Tool for Establishing Reliable and Qualitative Environmental Control Processes -- Advanced Clustering Analysis for Environmental Indicators -- Soknos An Interactive Visual Emergency Management Framework -- Visual Analytics -- Geospatial Visual Analytics -- Gis & Visual Analytics on Grid Technology -- Visual Analytics for the Strategic Decision Making Process -- Visual Analysis of Public Discourse on Environmental Issues -- Exploring Environmental News Via Geospatial Interfaces and Virtual Globes -- Spatio-Temporal Visualization for Environmental Decision Support -- Virtual Worlds and Spinning Globes -- Application of Virtual Worlds to Environmental Security -- Geographic Information Processing: Standards-Based Open Source Visualization Technology for Environmental Understanding -- Skylineglobe: 3D Web Gis Solutions For Environmental Security and Crisis Management -- Continental, National Regional, Local Experiences Case Studies -- The Challenge of a Spatial Data Infrastructure for the Mediterranean Islands -- A Distributed Real-Time Monitoring System for Landslide Hazard and Risk Assessment -- Validity of Drastic and SI Vulnerability Methods -- Environmental Security and Pastoralism -- Investigation Processes at the Kato Souli Basin -- Estimate of Soil Erosion in Jordan by Using GIS -- Data Access for Environment Protection and Economic Development -- Remote and in Situ Sensing for Dike Monitoring: The Ijkdijk Experience -- Political, Economical and Social Factors in the Protection of the Environment -- Environmental Protection VS. Eco & Environmental Terrorism: Threats, Impact and Contingency Plans -- Geopolitics and Environmental Security -- Illegal Trafficking of Waste in the Light of National and International Legislation.
Keywords: Earth sciences; Geology; Environmental sciences; User interfaces (Computer systems).; Computer graphics; Geographical information systems; Earth Sciences; Environmental Science and Engineering; User Interfaces and Human Computer Interaction; Geology; Environmental Monitoring/Analysis.; Geographical Information Systems/Cartography.; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books